A Malawi Church History 1860 - 2020 - Ross, Kenneth R. ca. 20./21. Jh. (MZUNI Press, 2020)
Cover -- Copyright page -- Title page -- Acknowledgments -- Foreword -- Contents -- Introduction -- Founding Charisms 1860 -- 1910 -- Chapter 1 -- Livingstone and Friends in Malawi -- Zambezi Expedition -- The UMCA at Magomero -- Halala Livingstone! -- Further Reading -- Chapter 2 -- Faith Taking Roots: Livingstonia Mission -- The African Lakes Company -- Connecting with Tonga and Ngoni -- Education and Revival -- Further Reading -- Chapter 3 -- Faith in the Vernacular: Blantyre Mission -- Emergence of an African Church -- Blantyre Mission and Colonial Rule -- Faith in the Vernacular